Development of Scratch Assisted E-Learning Teaching Materials on Wave Materials - Al Asy'Ari, Hasan; Hardyanto, Wahyu; Darsono, Teguh (Physics Communication, 2021)
This study aims to produce e-learning teaching materials that can be used to improve students' conceptual understanding. Teaching materials were made using scratch, which are integrated into web with the subject of physics subject waves for class XI. The type of research was Research and Development. The teaching materials developed have been implemented on a small scale, which was class XI students at MA Uswatun Hasanah Semarang. Data collection was carried out by giving the teacher a feasibility sheet for teaching materials. Data on students' conceptual understanding abilities were obtained from the results of pretest and posttest on a small scale, namely students of class XI MA Uswatun Hasanah Semarang and by looking for student or teacher responses to the teaching materials developed. Based on the experts and teachers’ assessment, the teaching materials developed were feasible. The implementation of teaching materials in physics learning on wave materials showed that the increase in students' conceptual understanding in the experimental class by using scratch-assisted e-learning teaching materials got a score of 0.52 (medium) better than the control class which used student worksheets to get a score of 0,34 (medium). In addition, students and teachers responded well to the developed teaching materials.